Public deliberation in Korean society: Where it stands and should head toward - Soo Kyeong Hwang (Korea Development Institute (KDI), 2022)
Public deliberation has demonstrated its potential as a conflict resolution mechanism through deliberative discourses on Shin-Kori nuclear power plant units 5 and 6 and the college admissions reform. However, these deliberative processes revealed some flaws in representativeness, inclusiveness, and the derivation of social consensus building through deliberation. In light of growing efforts to incorporate it into public decision-making, there is also an increasing need for proficiencies in systematic planning, support, and oversight.
Keywords: 330